Pengaruh Customer Relationship Management dan Sosial Media Marketing Instagram terhadap Tingkat Kunjungan - Andini Ramadani; Burhanuddin Burhanuddin; Muh. Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Zainal Ruma (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to determine the influence of Customer Relationship Management (CRM) and Instagram social media marketing on visit levels. The independent variables in this research are Customer Relationship Management (CRM) and Instagram social media marketing. The dependent variable in this study is the visit level. The population in this study was visitors to Makassar City Culture Service activities starting from January-February 2023, totaling 82,326 people. The sample in this study was selected using the Hair's method, with a total sample size of 120 respondents. The analytical method used in this research is the multiple linear regression analysis method. The results of this research show that Customer Relationship Management (CRM) has a positive and significant effect on the level of visits to the Makassar City Cultural Service, Instagram social media marketing has a positive and significant effect on the level of visits to the Makassar City Cultural Service, and simultaneously Customer Relationship Management (CRM) and Instagram social media marketing has a positive and significant effect on the level of visits to the Makassar City Culture Service.